Folk Musical Instruments in Bosnia and Herzegovina. - Talam, Jasmina (Cambridge Scholars Publishing, 2013)
Folk Musical Instruments in Bosnia and Herzegovina gives a complex and complete overview of traditional practice, for the first time, concerning traditional folk instruments on the territory of Bosnia and Herzegovina. The first part of the book describes historical sources and the research of folk musical instruments in Bosnia and Herzegovina. The research of history is one of the starting points in the process of organological research and covers careful research of historical documents, ph ...